Optimization of Barium Sulfate (BaSO₄) Crystallization Using the Box-Behnken Design Method to Mitigate Scaling in Industrial Pipes - Fatra, Fahmy; Abdillah, Fuad; Mahendra, Sena (Jurnal Rekayasa Mesin, 2025)
The precipitation of barium sulfate (BaSO4) in industrial piping systems is a major problem because it causes blockage, decreased productivity, and structural damage, including pipe rupture. Although there has been progress in understanding the mechanism of BaSO4 formation, some elements, such as the interaction of tartaric acid with BaSO4 crystals, the best parameters for reducing scaling, and the effectiveness of gas hydrate inhibitors, are still not fully understood. The objectives of this study were to find out how tartaric acid and BaSO4 crystals interact, find the ideal parameters to prevent scale formation, and assess the effectiveness of scaling inhibition techniques using gas hydrate inhibitor and scaling theories. This study used a Box-Behnken experimental design in the laboratory to optimize the temperature, solution concentration, and tartaric acid additive. The test was carried out under laminar flow conditions with a flow rate of 30 mL/min. After that, the morphology and composition of the scale were analyzed by SEM-EDX and XRD. The main results of the study showed that, under ideal conditions, the addition of tartaric acid significantly prolonged the induction time and reduced the mass of BaSO4 scale by up to 50%. This study reached the main conclusion that tartaric acid functions well as an anti-scaling agent and that ideal parameters can be used to effectively prevent scaling. This study is very helpful in developing more efficient and sustainable BaSO4 scaling mitigation methods for industrial applications.